A new method for the estimation of H-c2 anisotropy in polycrystalline MgB2 samples - Pissas, M.; Stamopoulos, D.; Koutantos, S. (JOURNAL OF SUPERCONDUCTIVITY, 2004)
By using isothermal magnetization measurements in polycrystalline MgB2 samples, we estimate the H-c2(c) in the interval [0, T-c]. By combining these measurements to the estimated H-c2(ab) from the onset of the diamagnetic transition in isofield and isothermal magnetic measurements, an estimation of the anisotropy parameter can be achieved. The H-c2(c) values coming from high quality polycrystalline samples agrees nicely to those obtained on single crystals. Our results show a temperature variation of the gamma(T) = H-c2(ab) / H-c2(c) with gamma(T-c) approximate to 3.